Krisis Pendidikan Keagamaan Buddha di Bali: Analisis Kebijakan Terhadap Keterbatasan Jumlah Guru Agama Buddha - Ida Royana (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy article examines the crisis in Buddhist religious education in Bali, a multidimensional issue rooted in teacher shortages and inefficient government policies. This study deeply analyzes the factors causing this crisis and formulates relevant policy alternatives. Root cause analysis, using a fishbone approach, indicates that the main problem lies in the limited number of teacher formations and appointments triggered by disproportionate formation policy regulations, as well as the slow policy response to the dynamics of teacher needs in the region. Based on the USG (Urgency, Seriousness, Growth) analysis, this problem has the highest priority level, demanding immediate and sustainable solutions. Therefore, a combination of strategic policies is recommended, including: (1) prioritizing the appointment of honorary teachers to PPPK; (2) implementing a rotation system with special incentives; (3) reforming formation allocation based on real needs data; and (4) simplifying the recruitment process through digitalization, and launching a campaign to increase the attractiveness of the teaching profession. The implementation of these recommendations is expected to overcome the crisis, guarantee the right to equal religious education for every Buddhist student, and strengthen the spiritual foundations within Balinese society.